2014
DOI: 10.1007/s00253-014-6038-3
|View full text |Cite
|
Sign up to set email alerts
|

The environment shapes microbial enzymes: five cold-active and salt-resistant carboxylesterases from marine metagenomes

Abstract: Most of the Earth's biosphere is cold and is populated by cold-adapted microorganisms. To explore the natural enzyme diversity of these environments and identify new carboxylesterases, we have screened three marine metagenome gene libraries for esterase activity. The screens identified 23 unique active clones, from which five highly active esterases were selected for biochemical characterization. The purified metagenomic esterases exhibited high activity against α-naphthyl and p-nitrophenyl esters with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 87 publications
2
72
0
2
Order By: Relevance
“…These chemicals included 11 model esters (7 pNP esters and 4 triacylglycerols) (Fig. 4), as well as a battery of 120 structurally different esters (3,6,27,28,37,53) (Fig. 5).…”
Section: Metagenome Library Construction and Screening For Carboxyl Ementioning
confidence: 99%
See 2 more Smart Citations
“…These chemicals included 11 model esters (7 pNP esters and 4 triacylglycerols) (Fig. 4), as well as a battery of 120 structurally different esters (3,6,27,28,37,53) (Fig. 5).…”
Section: Metagenome Library Construction and Screening For Carboxyl Ementioning
confidence: 99%
“…Based on a calculation of the apparent enantiomeric ratios for separate enantiomers (6), the enantiomeric ratios and substrate preferences are tentatively the following: Substrate fingerprints: comparison with known enzymes. The substrate profiles of the enzymes reported in this study against a set of 131 ester substrates (see the section on materials and methods in the supplemental material) were compared to a set of wellcharacterized commercial preparations with high substrate versatility (including CalA, CalB, Novozym 388 L, and PLE) and a set of carboxyl esterases obtained via genomic mining of marine bacteria (ABO_1197, ABO_1251, CCSP0084, CCSP0211, CCSP0528, and CCSP2178) or via metagenomic approaches of communities from marine (27,28) and brackish sediment samples (6).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Obvious examples are coldadapted (Berlemont, Pipers et al 2011, Jansson and Tas 2014, Martinez-Martinez, Lores et al 2014, Tchigvintsev, Tran et al 2014) and heat-adapted (Xia, Ju et al 2013 enzymes that have been identified and isolated from extremely cold and hot habitats, respectively. The isolated extremozymes have definite industrial applications ).…”
Section: Sampling Metagenomes: Random or Intuitivementioning
confidence: 99%
“…It was demonstrated that metagenomes are also promising sources for novel enzymes (23). However, there are only seven examples of polyester-hydrolyzing enzymes from metagenomic sources, including the LC-cutinase from a leaf-branch compost metagenomic library, which is capable of hydrolyzing not only cutin but also PET (24), the PLA depolymerase PlaM4, which is also from a compost metagenome (25), and five esterases from marine metagenomic libraries with hydrolytic activities toward several polyester substrates, including PLA (26). The potential of plant-associated metagenomes as a source of novel enzymatic activities has been less well explored (27).…”
mentioning
confidence: 99%